LEGALITAS HADIS TERHADAP UNDANG-UNDANG NOMOR 11 TAHUN 2020 TENTANG CIPTA KERJA - Maryus Suprayadi; Adi Faizun (Al-Afkar : Jurnal Keislaman & Peradaban, 2022)
There are many problems about the Job Creation Law like the different views with chapter 87 for examples, this chapter talking about free cost for anybody to make business license. Different with chapter 92 as no talking about free cost only but there is a possibility to someone using low cost to make that business licensi. Trying to untangle the tangled threads, the researcher will to finding some hadits to given the legislation of the Job Creation Law. This study applies a qualitative approach sourced from literature and legal jurisprudence. The focus of this research is to examine the relationship between hadith sources and several articles containing significant polemics contained in Law no. 11 of 2020 concerning Job Creation, including in the legal polemic against the doctrine of merging several regulations that were previously still thematic, which are considered more constitutional and easier for the legal community to digest, including legal practitioners. There are six points of legal substance that the author considers dominant in the elaboration of the Job Creation Act, namely guaranteeing rights and legal certainty, reorienting UMKM and ease of doing business, the spirit of togetherness and independence, employment opportunities and development, research and technology development and investment expansion, and opportunitiesdiversification of processing areas. From this research, it is found that the Job Creation Act implies empowering the Indonesian people in all sectors of work and employment. In addition, the form of hadith legislation in the Job Creation Law is found in, among other things, the principles of the formation of the law, the purpose of its formation, and the main problems with the law